Data analysis and business modeling with Excel 2013 manage, analyze, and visualize data with Microsoft Excel 2013 to transform raw data into ready to use information /: manage, analyze, and visualize data with Microsoft Excel 2013 to transform raw data into ready to use information. (2015) - Rojas, David
No abstract available